The North (ṣāpôn) in the Book of Jeremiah - Crouch, Carly L. 1982- (2023)
The »foe from the north« is a well-known trope in the book of Jeremiah. In 1989 David Reimer argued that this enemy should be understood as a nonspecific earthly enemy, with mythical overtones deriving from the location of Yhwh ’s divine abode on Mount Zaphon. Contemporary historiographical debates, together with Otto Eißfeldt’s arguments for an Israelite tradition of a »mythischen Nordberg«, exerted significant influence on Reimer’s discussion. This article examines these presuppositions, reconsiders the evidence, and argues that Jeremiah’s enemy »from the north« is a simple geographical reference to the Babylonian Empire.
Der »Feind aus dem Norden« ist eine bekannte Trope im Jeremiabuch. 1989 vertrat David Reimer die These, dieser Feind sei als unspezifischer irdischer Feind zu verstehen, wobei ein gewisser mythischer Unterton von der Lokalisierung der Wohnstätte Jhwhs auf dem Berg Zaphon herrühre. Gegenwärtige historiographische Debatten sowie Otto Eißfeldt’s Plädoyer für die Existenz einer israelitischen Tradition vom »mythischen Nordberg« beeinflussten Reimers Diskussion in signifikanter Weise. Der vorliegende Artikel untersucht diese Vorannahmen, erwägt den Befund neu und argumentiert, dass es sich bei Jeremias Feind »aus dem Norden« um eine einfache geographische Referenz auf das Babylonische Reich handelt., »L’ennemi du nord« est un motif bien connu du livre de Jérémie. En 1989, David Reimer a défendu la thèse que cet ennemi devait être compris comme un ennemi terrestre non spécifique, avec des connotations mythiques liées à l’emplacement de la demeure divine de Yhwh sur le mont Tsaphon. Les débats historiographiques contemporains, ainsi que les arguments d’Otto Eissfeldt en faveur d’une tradition israélite d’un »mythischer Nordberg«, ont exercé une influence significative sur la discussion de Reimer. Cet article examine ces présupposés, reconsidère les preuves et soutient que l’ennemi de Jérémie »venant du nord« est une référence géographique à l’Empire néo-babylonien.